Estimates of demographic parameters for southern right whales (Eubalaena australis) observed off Pen´ınsula Vald´es, Argentina - Cooke, J. G.; Rowntree, V. J.; Payne, R. (J. Cetacean Res. Manage., 2020)
Photographs of the right whales which occur between June and December in the waters surrounding Pen´ınsula Vald´es, Argentina, have been obtained from aerial surveys conducted each year from 1971 to the present. Resightings of previously catalogued individuals enable various demographic parameters to be estimated. From analyses of multiple resightings of females accompanied by calves, estimates of the following demographic parameters were obtained, based on the data collected during 1971-90: mean calving interval 3.35 yrs (SE = 0.05 yrs); mean age at first calving 9.1 yr (SE = 0.3 yr); adult female annual mortality rate 0.019 (SE = 0.005); annual percentage rate of population increase 6.9% (SE = 0.7%); reproductive female population size in 1990: 328 animals (SE = 21). No evidence of any trend with time in mean calving interval, mortality rate or rate of population increase was found.